Erythroid expression of the heme-regulated eIF-2 alpha kinase. - Crosby, J S (1994)
The role of heme-regulated eIF-2 alpha kinase (HRI) in the regulation of protein synthesis in rabbit reticulocytes is well documented. Inhibitors of protein synthesis with properties similar to those of HRI have been described in some nonerythroid cell types, but it has not yet been determined whether these eIF-2 alpha kinase activities are mediated by HRI or one or more as yet uncharacterized kinases. We have studied the expression of mRNA, polypeptide, and kinase activities of HRI in various tissues from both nonanemic and anemic rabbits. Our results indicate that HRI is expressed in an erythroid cell-specific manner. HRI is present in the bone marrow and peripheral blood of both nonanemic and anemic rabbits but not in any of the other tissues tested. HRI mRNA is present at low levels in uninduced mouse erythroleukemic (MEL) cells and human K562 cells and accumulates to higher levels upon induction. The accumulation of HRI mRNA in differentiating MEL cells is dependent upon the presence of heme. The addition of 3-amino-1,2,4-triazole (AT), an inhibitor of heme biosynthesis, to the induction medium markedly reduced HRI mRNA accumulation. Simultaneous addition of hemin and AT to the dimethyl sulfoxide induction medium largely prevented the inhibition of HRI mRNA induction by AT. These findings indicate that HRI is expressed in an erythroid cell-specific manner and that the major physiologic role of HRI is in adjusting the synthesis of globins to the availability of heme.